2008
DOI: 10.1038/msb.2008.54
|View full text |Cite
|
Sign up to set email alerts
|

A competitive complex formation mechanism underlies trichome patterning on Arabidopsis leaves

Abstract: Trichome patterning in Arabidopsis serves as a model system for de novo pattern formation in plants.It is thought to typify the theoretical activator-inhibitor mechanism, although this hypothesis has never been challenged by a combined experimental and theoretical approach. By integrating the key genetic and molecular data of the trichome patterning system, we developed a new theoretical model that allows the direct testing of the effect of experimental interventions and in the prediction of patterning phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(152 citation statements)
references
References 47 publications
3
147
1
1
Order By: Relevance
“…Nevertheless, the results presented here do not exclude the possibility that other flowering factors also participate in controlling trichome formation in specific floral organs. In the lateral inhibition model proposed for rosette leaf trichome pattering, the negative regulator genes, such as TRY, are activated in trichome cells by the GL1-GL3-TTG1 protein complex and moved to neighboring cells to repress trichome initiation (Schellmann et al, 2002;Digiuni et al, 2008). Consistent with GL1, the TRY expression in rosette leaves is also trichome specific (Schellmann et al, 2002;Esch et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the results presented here do not exclude the possibility that other flowering factors also participate in controlling trichome formation in specific floral organs. In the lateral inhibition model proposed for rosette leaf trichome pattering, the negative regulator genes, such as TRY, are activated in trichome cells by the GL1-GL3-TTG1 protein complex and moved to neighboring cells to repress trichome initiation (Schellmann et al, 2002;Digiuni et al, 2008). Consistent with GL1, the TRY expression in rosette leaves is also trichome specific (Schellmann et al, 2002;Esch et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The singlerepeat MYB proteins can move from the trichome into neighboring cells where they compete with GL1 for the binding site of GL3 to prevent the formation of the active protein complex, resulting in blockage of trichome initiation. This lateral inhibition mechanism explains how the trichome spacing pattern is generated in rosette leaves (Schellmann et al, 2002;Digiuni et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…B) SEM of trichomes (protective hairs) on the underside of a leaf of Arabidopsis; image from Deeks et al (2007), with permission. Digiuni et al (2008) found that trichomes are patterned by an RD mechanism, by quantitatively matching experimental manipulations of specific trichome genes with a dynamic (RD) model of trichome gene interactions.…”
Section: Patterning Of Multicellular Whorls: Conifer Embryogenesismentioning
confidence: 97%
“…Several groups have recently published work on RD mechanisms in specific genetic pathways in Arabidopsis development, identifying specific known molecules as Turing morphogens. Digiuni et al (2008) determined that trichomes, protective hairs on the undersides of Arabidopsis leaves (Fig. 9B), are patterned by an RD mechanism.…”
Section: Rd In Plant Geneticsmentioning
confidence: 99%
“…Various models have been proposed including (a) activator-inhibitor reaction-diffusion (AIRD) PDEs models [13], (b) cellular signaling and switching models [7,25], (c) phenomenological genetic models-logical descriptions of the gene activity in terms of diagrammatic models, and (d) systems of ordinary differential equations which model the known genetics and a biological interpretation of the roles of the genes [6].…”
Section: Introductionmentioning
confidence: 99%